Experiential quality among coffee lovers : an empirical study in the Malaysian coffee outlets industry - Suguna Sinniah; Gopal Perumal; Ravindaran Seniasamy; Paul Anthony Maria Das; Ramesh Kumar Moona Haji Mohamed; Oruwalage Sandalu Dhananjaya (Penerbit Universiti Kebangsaan Malaysia, 2018)
Experiential Quality has become extremely important for coffee outlets industry due to the highly competitive environment. The main objective of this study is to analyze the quality of the coffee outlets to win more customers in Malaysia. This study specifically design to investigate the existing literature on experiential quality comprising Interaction quality, Physical environment quality, Outcome quality and Affective quality. Researcher used a self-administrated questionnaire survey with a sample size of 200 respondents from various coffee outlets in Selangor, Malaysia (One of the state with high population in Malaysia). The Findings shows that Interaction quality, Physical environment quality, and Outcome quality have direct effect on experimental quality among coffee lovers. Affective quality shows an negative effect on experiential quality. Coffee is one of the global product. Coffee sold at branded coffee outlets are niche market product. Coffee outlets industry is a classified destination of consumers with intrinsic value of coffee. Coffee outlets offer typical coffer qualities in attractive environment to withhold coffee lovers. This special product is consumed by middle income and higher income social class consumers. The findings further implied coffee outlets focused at managing coffee lovers’ service quality expectation to create and enlarge greater coffee loyalist for sustainable competitive advantage.